Exploring The Impact of Dynamic Learning Capabilities on Career Skill of Generation Z - Sholikah, Mar'atus; Marpaung, Afni Atika (Universitas Negeri Surabaya, 2024)
The objective of this study is to examine the influence of absorptive capability, innovative capability, and self-learning capability on the development of career skills of generation Z office/business administration graduates and prospective graduates in Indonesia. The study used a quantitative approach and a cross-sectional survey method to collect data from 100 respondents in Central Java. The respondents were graduates and prospective graduates of office/business administration. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method to test the relationship between latent variables. The findings of the study suggest that the three primary variables (i.e., absorptive capability, innovative capability, and self-learning capability) exert a positive and significant influence on the development of career skills. Furthermore, it was determined that innovative capability and self-learning capability significantly mediate the relationship between absorptive capability and career skills. This study offers a theoretical contribution by expanding the application of dynamic capabilities theory to the realm of individual development. The practical implications of this study are twofold: first, it can serve as a foundational basis for the development of competency development strategies in graduate education and industry; and second, it can equip Generation Z with the relevant skills necessary for the future of work.